A global analysis of the value of precision medicine in oncology – The case of non-small cell lung cancer - Hofmarcher, Thomas; Malmberg, Chiara; Lindgren, Peter (Frontiers in Medicine, 2023)
Objectives: Biomarker testing is indispensable for the implementation of precision medicine (PM) in oncology. The aim of this study was to assess the value of biomarker testing from a holistic perspective based on the example of advanced non-small cell lung cancer (aNSCLC). Methods: A partitioned survival model was populated with data from pivotal clinical trials of first-line treatments in aNSCLC. Three testing scenarios were considered; ‘no biomarker testing’ encompassing chemotherapy treatment, ‘sequential testing’ for EGFR and ALK encompassing treatment with targeted- or chemotherapy, and ‘multigene testing’ covering EGFR, ALK, ROS1, BRAF, NTRK, MET, RET and encompassing treatment with targeted- or immuno(chemo)therapy. Analyses of health outcomes and costs were run for nine countries (Australia, Brazil, China, Germany, Poland, Japan, South Africa, Turkey, United States). A one-year and five-year time horizon was applied. Information on test accuracy was combined with country-specific information on epidemiology and unit costs. Results: Compared to the no-testing scenario, survival improved and treatment-related adverse events decreased with increased testing. Five-year survival increased from 2% to 5-7% and 13-19% with sequential testing and multigene testing, respectively. The highest survival gains were observed in East Asia due to a higher local prevalence of targetable mutations. Overall costs increased with increased testing in all countries. Although costs for testing and medicines increased, costs for treatment of adverse events and end-of-life care decreased throughout all years. Non-health care costs (sick leave and disability pension payments) decreased during the first year but increased over a five-year horizon. Conclusion: The broad use of biomarker testing and PM in aNSCLC leads to more efficient treatment assignment and improves health outcomes for patients globally, in particular prolonged progression-free disease phase and overall survival. These health gains require investment in biomarker testing and medicines. While costs for testing and medicines would initially increase, cost decreases for other medical services and non-health care costs may partly offset the cost increases.